2016
DOI: 10.1177/1049732315609567
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned Designing and Using an Online Discussion Forum for Care Coordinators in Primary Care

Abstract: While an increasing number of researchers are using online discussion forums for qualitative research, few authors have documented their experiences and lessons learned to demonstrate this method's viability and validity in health services research. We comprehensively describe our experiences, from start to finish, of designing and using an asynchronous online discussion forum for collecting and analyzing information elicited from care coordinators in Patient-Centered Medical Homes across the United States. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…This could provide useful insights, for example into women's concerns about pool use, an area little explored in previous research. Furthermore, although utilising online discussion groups enabled access to a geographically diverse population, this method may have resulted in sampling bias through excluding those with low levels of digital literacy (Ferrante et al., 2016). To enhance security of the online groups, registration was a two-stage process, which may have been a barrier to participation.…”
Section: Discussionmentioning
confidence: 99%
“…This could provide useful insights, for example into women's concerns about pool use, an area little explored in previous research. Furthermore, although utilising online discussion groups enabled access to a geographically diverse population, this method may have resulted in sampling bias through excluding those with low levels of digital literacy (Ferrante et al., 2016). To enhance security of the online groups, registration was a two-stage process, which may have been a barrier to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Other than this and their ability to create forum threads, no other distinction was made between them and participants. This is different from other online discussion studies, such as Ferrante et al (), who defined moderators “as someone who would clarify postings, elicit elaboration or explanation, foster interaction, encourage reflection, keep participants on track, offer support, and enforce the rules of engagement” (p. 1854). The moderators aimed to create a community of individuals working toward a shared goal, who shared similar journeys and experiences – and endeavored to avoid power inequities which would emphasize differences.…”
Section: Building the Online Communitymentioning
confidence: 82%
“…Previous research has observed that an increasing number of researchers are designing online discussion forums for qualitative health research, and yet there is limited literature in which researchers have documented their experiences and lessons learned to demonstrate the viability and validity of this method (Ferrante et al, ). In this article, we report our experiences in an effort to ameliorate this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Participants could choose from the categories outlined in Figure 2, with a change in direction towards more people being involved labelled as 'widening', the inverse as 'narrowing'. Online methods of discussion are appropriate where a group of people is geographically dispersed and face to face discussion is impractical 32 . We selected an asynchronous online discussion format for this study as it allowed flexibility, especially regarding participants contributing from different time-zones.…”
Section: Methodsmentioning
confidence: 99%